Change in local regulation of hemopoiesis under the chronic exposure to ionizing radiation - Ya. V. Porovsky (Бюллетень сибирской медицины)
Results of annual examinations of peripheral blood and single examinations of bone marrow after 11, 14, 15, and 22 years of the chronic exposure to ionizing radiation in total doses of 24.25, 103.96, 111.84, and 74.09 mSv, respectively, are presented along with the results on the morphology of microvasculature vessels in skin tissue samples of two men and two women working at a nuclear reactor. Changes in the content of hemoglobin, total number of leucocytes, population of erythrocytes, neutrophils, reticulocytes, and in the composition of maturating and mature myeloid and erythroid cells accompanied by an increase составе in the number of cells of the lymphoid and monocytic pool as the intensity of inflammatory changes in microvasculature vessels increases from productive panvasculitis to panvasculitis with sclerosis of vessel wall were noticed. The presented actual material indicates that damages in the blood system can be connected with the intensity of pathological changes in microvasculature vessels, which represent one of the local components of hemopoiesis-inducing microenvironment responsible for hemopoiesis regulation.